Brand loyalty on Fast Moving Consumer Goods (FMCG) among office workers in Kuala Lumpur / Nurul Aida Mohamad Nizam - Mohamad Nizam, Nurul Aida (Faculty of Business and Management, 2019)
The purpose of this research is to identify the determinants that effect Brand Loyalty on Fast Moving Consumer Goods (FMCG) Among Office Workers in Kuala Lumpur. This study was conducted to know the relationship between independent (Brand Trust, Brand Association, Brand Personality and Brand Awareness) variable and dependent variable where it is correlated with each other. Hence with the proper observation, its aim study aims to investigate the major factors that influence Brand Loyalty on Fast Moving Consumer Goods (FMCG) Among Office Workers in Kuala Lumpur. The first objective is to examine the relationship with brand trust and Brand Loyalty on Fast Moving Consumer Goods (FMCG) Among Office Workers in Kuala Lumpur. Secondly, to analyze the relationship with brand association and Brand Loyalty on Fast Moving Consumer Goods (FMCG) Among Office Workers in Kuala Lumpur. Thirdly, to investigate the relationship with brand personality and the Brand Loyalty on Fast Moving Consumer Goods (FMCG) Among Office Workers in Kuala Lumpur. Lastly, it was to observe the relationship with brand awareness and brand loyalty consumers toward Brand Loyalty on Fast Moving Consumer Goods (FMCG) Among Office Workers in Kuala Lumpur. The sampling design that used in this research is non- probability sampling which is the convenient sampling. The data collection method are primary data and secondary data which the primary data are conducted by distributed a questionnaire to the sample size where 200 respondent at the Tabung Haji HQ which is the staff. The finding and research were result in frequency, descriptive, correlation and regression. Finally, the data, conclusions and recommendations are conducted.